Identification and transcriptional profiling of UV-A-responsive genes in Bemisia tabaci - Muhammad Musa Khan; Dylan O’Neill Rothenberg; Shahfahad; Bao-Li Qiu; Zeng-Rong Zhu (Ecotoxicology and Environmental Safety, 2023)
Ultraviolet-A (UV-A) radiation directly impacts the growth and spread of Bemisia tabaci. However, the mechanistic pathways of this phenomenon remain unknown. We analyzed B. tabaci transcriptome data after exposure to UV-A radiation for 6 h. The 453 genes were identified whose expression were significantly altered in response to the stress induced by UV-A irradiation. Forty genes were up-regulated, while 413 genes were down-regulated. Enrichment analysis using GO, KEGG, and Genomes databases revealed that the DEGs play key roles in antioxidation and detoxification, protein turnover, metabolic, developmental processes, and immunological response. Among the gene families involved in detoxification, shock, and development, down-regulated DEGs in transcriptional factor gene families were significantly greater than those up-regulated DEGs. Our findings demonstrated that exposure to UV-A stress can suppress immunity and affect the growth and biological parameters of B. tabaci by altering gene regulation. These results suggest a potential utility of UV-A stress in managing B. tabaci under greenhouse conditions.